Gambaran Kesiapsiagaan Mayarakat Menghadapi Bencana Gunung Meletus di Dukuh Gebyog Samiran Selo Boyolali - Avica Miftakhul Jannah; Irma Mustika Sari (Yayasan Literasi Sains Indonesia, 2023)
Throughout 2018, Indonesia experienced 10 volcanic eruptions. The volcanic eruption became one of the domicile disasters in 2018. In 2019 there were 7 volcanic eruptions in the last 1 year. Volcanic eruptions that threaten and disrupt people's lives and livelihoods are caused by natural or non-natural factors that result in casualties, environmental damage, loss of property, and psychological impacts. Boyolali Regency is one of the districts that are prone to volcanic eruptions in Central Java Province. The number of relative disasters continues to increase from year to year in Boyolali City which has a location prone to volcanic disasters, especially in Selo Village. The purpose of this study was to describe the preparedness of the community to face the Mount Meletus disaster in Gebyog Samiran Village, Selo Boyolali. The type of research used is a descriptive research and the method used is a descriptive survey. The sampling technique in this study uses simple random sampling with a sample of 53 respondents. The results showed that based on the characteristics of the respondents, the majority were in the age range of 41-60 years (39.6%), female sex was (62.3%), education level was in elementary school (54.7%), and worked as a farmer (50.9%). Meanwhile, the majority of residents were in the ready category (37.7%). The description of community preparedness to face the Mount Eruption disaster in Gebyog Hamlet, Samiran Selo Boyolali, is mostly in the ready category (52.8%).